One new occurrence species of the genus Rungia Nees (Acanthaceae ) for the flora of Vietnam - Xuyen, Do Thi; Hai, Do Van (Academia Journal of Biology, 2014)
The genus Rungia Ness (Acanthaceae) has approximately 50 species in the world, mainly distributing in the tropical. In Vietnam, it has 4 species. During the study of the Acanthaceae specimens of Vietnam, we have found Rungia chinensis Benth. (Acanthaceae) as a new record for the flora of Vietnam. It is a herb to 40 cm or more; slender, puberenlent; leaves broadly ovate to oblong-ovate, 2-4 cm long, 1-3 cm wide; lateral veins 4-5 per side; petioles 1-3 cm long. Spikes terminal or axillary, 3-6 cm long; outer bracts elliptic, ca. 6 mm long, 2-4 mm wide, sparingly ciliate; inner bracts broadly obovate or obovate-oblong, 0.7-0.8 mm long, 0.2-0.4 cm wide; brateoles ovate, 0.6-0.7 cm long, 0.4-0.5 cm wide, apex acuminate, margins hyalin, sparingly ciliate; calyx 5 lobed, segments linear-lanceolate; corolla pale purple or white, 6-8 mm long with 2 lips, lower lip 3 lobed; filaments up to 0.5 cm long, hirsute at base; style to 0.7-1 cm long, glabrous; stigma obtuse. Capsule ovoid, ca. 0.6 cm long. It is close to R. pierrei Benoist but only differs from it in leaves broadly obvate to obvate-oblong, 2-4 cm long; bracteole margins hyaline. The specimens were collected in the Lamdong province (Lacduong district), Vietnam by Le Dong Tan et al. and deposited in the Hanoi herbarium, Institute of Ecology and Biological resources, Hanoi, Vietnam (HN).